Ultrathin Ta2O5-coated super P carbon black as a stable conducting additive for lithium batteries charged to 4.9Vat 55°C. (June 2020) - Zhang, Hua; Ben, Liubin; Yu, Hailong; Qi, Wenbin; Zhao, Wenwu; Huang, Xuejie
Abstract: The carbon-conducting additive-induced degradation of the cycling performance of lithium-ion batteries needs to be carefully controlled, particularly at a high operating voltage and elevated temperature. Herein, we report the investigation of surface coating with 2–3 nm of Al2 O3, TiO2 and Ta2 O5 oxides on Super P carbon black via atomic layer deposition. Detailed step potential tests revealed that after storage in EC/DMC electrolyte for 14 days at 55 °C, the stability of Ta2 O5 -coated Super P was the highest compared with those of Al2 O3 - and TiO2 -coated counterparts. This result is attributed to Ta2 O5 acting as a HF barrier, which mitigates the oxidation of electrolyte on the surface of Super P, as observed by XPS, thus showing less deposition of carbonate species. Further experiments showed that the surface of the Ta2 O5 coating layer was stable, while the Al2 O3 and TiO2 coating layers were completely dissolved in dilute HF after storage for 12 h Ta2 O5 -coated Super P was verified in a LiNi0.5 Mn1.5 O4 half-cell charged to 4.9 V at 55 °C. The results showed that with Ta2 O5 -coated Super P as the conducting additive, the half-cell exhibited an improved coulombic efficiency of 99.5%, compared with 98.3% for the pristine Super P. Graphical abstract: Image 1